Antibacterial Properties of D-Amino Acid Oxidase: Impact on the Food Industry - Marcone, Giorgia Letizia; Binda, Elisa; Rosini, Elena; Abbondi, Monica; Pollegioni, Loredano (Frontiers in Microbiology, 2019)
Food quality is also related to safety and prevention of spoilage. Biological antimicrobial agents represent suitable alternatives to clinical preservatives in food industry to increase both safety and stability of aliments. Here we focused on the enzyme D-amino acid oxidase from the yeast Rhodotorula gracilis (DAAO), a well studied protein for biotechnological use based on its stability, high activity and easy recombinant production. DAAO catalyzes the O2-dependent oxidative deamination of D-enantiomer of amino acids generating -keto acids, ammonia and hydrogen peroxide. DAAO shows antibacterial activity on both Gram-positive and Gram-negative bacteria in the presence of D-alanine when tested on plates and reduced by half their growth when tested on liquid cultures. Control experiments performed with alternative amino acid-specific flavoenzymes (able or not to generate H2O2 acting on amino acids), a DAAO inactive variant, catalase (H2O2 scavenger) and L-amino acids instead of D-alanine identified H2O2 as the antibacterial agent. DAAO showed a good ability to decrease the bacterial growth on various food stuffs: e.g., 10-fold less colonies were formed on grated cheese incubated for 16 hours at 37 °C when a tiny amount (0.01 mg corresponding to 1.2 units) of DAAO was added. No exogenous D-amino acids were added since DAAO used the ones naturally occurring or the ones generated during ripening. Notably, simultaneously to H2O2 generation, DAAO also acts as O2-scavenger thus further hampering food deterioration.